Causes of Change Orders in Construction Projects - Khalifa, W. M. A.; Mahamid, I. (Engineering, Technology & Applied Science Research, 2019)
Change orders are usually issued to cover variations in the scope of work, material quantities, design errors, and unit rate changes. This study discusses variations in public construction projects in Saudi Arabia by investigating their causes, studying their effects on the project, identifying the beneficial parties, and suggesting remedies to alleviate the related problems. Tasks included conducting a field survey via a questionnaire. It was determined that the top five causes of change orders from contractors’ view are: owner’s additional works, errors, and omissions in design, lack of coordination between construction parties, defective workmanship, and owner financial difficulties.